Advances in rice seedling cultivation techniques in China: a comprehensive review - Yang, Xiaolian; Yang, Zeyu; Zhao, Chuan; Li, Guoliang; Li, Jiangtao (Frontiers in Plant Science, 2026)
Rice is crucial for China’s food security. Mechanized rice production offers advantages like labor-cost reduction, efficiency gains, and yield stability. In mechanized rice production, mechanized and high-efficiency seedling raising has consistently been a top priority, with three main methods: traditional paddy nurseries, greenhouse systems, and industrialized factory production. Factory-based systems use advanced tech, enabling full-process mechanization and intelligent monitoring, reducing seedling mortality. This review explores the development trends of rice seedling raising technology focusing on rice mechanical transplanting, as well as the innovation paths for future equipment.